2020
DOI: 10.1038/s41396-020-0674-7
|View full text |Cite
|
Sign up to set email alerts
|

Fruitbody chemistry underlies the structure of endofungal bacterial communities across fungal guilds and phylogenetic groups

Abstract: Eukaryote-associated microbiomes vary across host taxa and environments but the key factors underlying their diversity and structure in fungi are still poorly understood. Here we determined the structure of bacterial communities in fungal fruitbodies in relation to the main chemical characteristics in ectomycorrhizal (EcM) and saprotrophic (SAP) mushrooms as well as in the surrounding soil. Our analyses revealed significant differences in the structure of endofungal bacterial communities across fungal phylogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 80 publications
1
40
0
Order By: Relevance
“…At the genus level, numerous members of the Allorhizobium-Neorhizobium-Pararhizobium-Rhizobium complex were distributed in the fruit bodies of C. cibarius , which was consistent with the observations of ( Pent et al (2017 , 2020) , Rinta-Kanto et al (2018) , and Gohar et al (2020) . Together with other symbiotic bacteria, these genera may play a key role in maintaining the health of the fruit body ( Gohar et al 2020 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…At the genus level, numerous members of the Allorhizobium-Neorhizobium-Pararhizobium-Rhizobium complex were distributed in the fruit bodies of C. cibarius , which was consistent with the observations of ( Pent et al (2017 , 2020) , Rinta-Kanto et al (2018) , and Gohar et al (2020) . Together with other symbiotic bacteria, these genera may play a key role in maintaining the health of the fruit body ( Gohar et al 2020 ).…”
Section: Discussionsupporting
confidence: 87%
“…These authors suggested that the soil pH and host identity were the predominant factors affecting bacterial community composition. Pent et al (2020) continued to merge high-throughput sequencing and chemical composition determination to compare and analyze the chemical content and bacterial community composition of the fruit bodies of EMF, including C. cibarius , and revealed that the differences in the chemical composition of fruit bodies also markedly impacted bacterial community composition. Recently, Gohar et al (2020) analyzed bacterial community potential function variation at different development stages (young, middle-aged, and old) and in internal (cap, stipe lower internal, stipe middle internal) and external (gills, cap surface, stipe lower external, and stipe middle external) compartments of fruit bodies of C. cibarius , and compared the bacteria with that of other ectomycorrhizae.…”
Section: Introductionmentioning
confidence: 99%
“…As the field of bacterial-fungal interactions grows, we begin to understand the implications that these interactions have not only on the microorganisms, but also on plant and human hosts. This review shows that there are several areas of overlapping commonalities between BFIs in agriculture and clinical settings, including the use of fungal structures for bacterial dispersal [ 11 , 62 , 63 , 73 ], using ECM for bacterial attachment [ 14 , 18 ], and developmental changes that can occur in both fungi and bacteria [ 43 , 49 ] ( Figure 2 ). It is possible that there are even more commonalities that have yet to be discovered, including endosymbiosis in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial communities have been identified in ectomycorrhizal fungi and in saprotrophic mushrooms, where the community structure was dependent on the fungal phylogenetic groups. This variation has been attributed to variations in fruiting body chemistry, specifically to the C:N ratio and pH [ 43 ].…”
Section: Bacterial-fungal Physical Interactionsmentioning
confidence: 99%
See 1 more Smart Citation